2022
DOI: 10.3390/jpm12040593
|View full text |Cite
|
Sign up to set email alerts
|

Specific Therapy for T2 Asthma

Abstract: Asthma is a disease with high incidence and prevalence, and its severe form accounts for approximately 10% of asthmatics. Over the last decade, the increasing knowledge of the mechanisms underlying the disease allowed the development of biological drugs capable of sufficiently controlling symptoms and reducing the use of systemic steroids. The best-known mechanisms are those pertaining to type 2 inflammation, for which drugs were developed and studied. Those biological treatments affect crucial points of bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 95 publications
0
10
0
2
Order By: Relevance
“…[3,4] Over the last decade, increased knowledge of the mechanisms underlying the pathogenesis of asthma has facilitated the development of modern biological therapy for the treatment of severe asthma. [5,6] Modern biological therapy targets the pro-inflammatory cytokines or mediators, including IL-5, IL-4, IL-13/IL4, IgE, and thymic stromal lymphopoietin (TSLP). [7][8][9] TSLP is an epithelial cell-derived cytokine in the airways, belonging to the group of alarmins, that plays a central role in the pathogenesis of asthma by activating and maintaining downstream inflammatory processes in response to multiple triggers, including viruses, bacteria, fungi, allergens, pollutants, smoke, other airborne irritants, and physical injury.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Over the last decade, increased knowledge of the mechanisms underlying the pathogenesis of asthma has facilitated the development of modern biological therapy for the treatment of severe asthma. [5,6] Modern biological therapy targets the pro-inflammatory cytokines or mediators, including IL-5, IL-4, IL-13/IL4, IgE, and thymic stromal lymphopoietin (TSLP). [7][8][9] TSLP is an epithelial cell-derived cytokine in the airways, belonging to the group of alarmins, that plays a central role in the pathogenesis of asthma by activating and maintaining downstream inflammatory processes in response to multiple triggers, including viruses, bacteria, fungi, allergens, pollutants, smoke, other airborne irritants, and physical injury.…”
Section: Introductionmentioning
confidence: 99%
“…7 Excessive IL-13 secretion by airway Th2 cells stimulates AHR deterioration and increases airway mucus hypersecretion. 8 Therefore, in the respiratory system, reducing Th2-cell activation and increasing Th1-cell activation can potentially improve asthma attacks and relieve asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…12 The second category of asthma drugs is used to relieve and improve asthma attacks, and mainly comprises bronchodilators, including short-acting beta-agonists and anticholinergics. 8 Long-term use of oral or injectable steroids will produce a variety of side effects, and suppress immune system function, reducing the activities of Th1 cells and Th2 cells. 11 In recent years, many studies have shown that some natural products can regulate the activation of Th1 cells and Th2 cells, and improve the development of asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations